How and why do states provide for children? Comparing social grants for families with children in Southern Africa - Chinyoka, Isaac (Department of Sociology, 2019)
This thesis explores variation in public policy with a focus on the provision of social grants (social cash transfers) for families with children. The thesis investigates how and why three middle-income countries (South Africa, Namibia and Botswana) and a low-income country (Zimbabwe) in Southern Africa provide for children in different ways. In-depth interviews and desktop research established that ‘child welfare regimes’ (CWRs) (a combination of programmes affecting the welfare of children, primarily cash transfers, feeding programmes, health and education fee waivers) are similar in providing some form of social grants, directly and/or indirectly to children or families with children. But there are significant variations between the CWRs. The CWRs primarily vary across two dimensions: first, the coverage of programmes; and secondly, their targeting, specifically whether they are targeted on poverty or on perceived ‘family breakdown’. I present a taxonomy of CWRs with four distinct types: a pro-poor (poverty-targeted) CWR (as in South Africa), a familialist CWR (targeted on ‘broken’ families) (as in Botswana), a mixed (pro-poor-familial targeted) CWR (as in Namibia) and an agrarian (family-targeted) one (as in Zimbabwe). A pro-poor CWR is distinguished by high coverage and generous transfers. A familial CWR provides medium coverage with overall generosity but with parsimonious cash benefits. A mixed CWR has low coverage and modest generosity while an agrarian CWR has low coverage and ungenerous benefits. This taxonomy emphasises variation in targeting form, an important but underestimated dimension in identifying and explaining CWRs particularly in Southern Africa. In explaining the variation, the factors that were especially important include colonial antecedents, need or structural factors (particularly AIDSrelated health shocks, demographic changes and family breakdown), international influence by international organisations, particularly UNICEF, the level of democracy but all these factors and the choice for a CWR reflect domestic politics (party politics and civil society organisations). These findings extend the Power Resource Theory beyond developed countries but also reveal new influential factors, within the theory, that have been overlooked but significant in explaining variation between CWRs.